2010
DOI: 10.1029/2010gc003142
|View full text |Cite
|
Sign up to set email alerts
|

Silicate weathering machine at work: Rock magnetic data from the late Paleocene–early Eocene Cicogna section, Italy

Abstract: [1] We describe a scenario of climate forcing on sedimentation recorded in the late Paleocene-early Eocene Cicogna marine section from the Belluno Basin (NE Italy). Previously published magneto-biostratigraphic data revealed that the ∼81 m Cicogna section extends from Chron C25r to Chron C23r spanning the NP7/ NP8-NP12 nannofossil zones (∼52.2-56.6 Ma). Using previously published rock magnetic data, augmented by data from this study, we describe and thoroughly discuss a pronounced increase of hematite (relativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 75 publications
6
17
0
Order By: Relevance
“…After removal of these directions, all samples showed a stable characteristic ChRM magnetization linearly trending to the origin of the demagnetization axes and isolated up to 670 °C. This unblocking temperature suggests, together with previous rock‐magnetic data (Dallanave et al 2010), that this ChRM magnetization is carried by haematite. Only a single grey sample collected at −0.1 m, that is, before the onset of the PETM (Fig.…”
Section: Palaeomagnetismsupporting
confidence: 81%
See 3 more Smart Citations
“…After removal of these directions, all samples showed a stable characteristic ChRM magnetization linearly trending to the origin of the demagnetization axes and isolated up to 670 °C. This unblocking temperature suggests, together with previous rock‐magnetic data (Dallanave et al 2010), that this ChRM magnetization is carried by haematite. Only a single grey sample collected at −0.1 m, that is, before the onset of the PETM (Fig.…”
Section: Palaeomagnetismsupporting
confidence: 81%
“…during heating in nearly zero magnetic field (e.g. Kodama 1982; Wang et al 2004), as already observed in the Cicogna CMU (Dallanave et al 2010). The 0.1 T (low) coercivity curve shows instead a progressive intensity decline up to ∼650–670 °C, indicating the presence of pure maghemite characterized by low coercivities and Curie temperatures ranging from 590 to 675 °C (Tauxe 2010) although it could also be a lower coercivity form of haematite (specular haematite) as found by Tauxe et al (1980).…”
Section: Rock‐magnetismsupporting
confidence: 68%
See 2 more Smart Citations
“…One of the proposed possibilities for permanently sequestering carbon and lowering atmospheric CO 2 levels is the enhanced chemical weathering of silicate rocks and pedogenesis on the continents [ Zachos and Dickens , ]. So far, most reports about intensified weathering are indirectly from marine sediments [ Ravizza et al ., ; Kelly et al ., ; Dallanave et al ., ], whereas the only terrestrial records are from North America [ Clechenko et al ., ; Kraus and Riggins , ; White and Schiebout , ]. In this study, the evolution of major‐element contents and clay minerals provides another direct terrestrial evidence to attest the silicate‐weathering mechanism.…”
Section: Discussionmentioning
confidence: 99%